Northbound migration count of raptors at Tanjung Tuan, Peninsular Malaysia: magnitude, timing, and flight behavior - Puan, Chong Leong; Yeap, Chin Aik; Lim, Kim Chye; Lim, Aun Tiah; Khoo, Swee Seng; Cheung, Nina (Raptor Research Foundation, 2014)
Tanjung Tuan is a primary spring raptor migration watchsite in Malaysia. During northbound migration, many raptors can be seen crossing the Straits of Malacca from Sumatra (Indonesia) to Peninsular Malaysia. We examined the migration magnitude, timing, and flight behavior of migratory raptors recorded based on migration counts at Tanjung Tuan in 2009 and 2010. A total of 37 615 migrating raptors of 11 species and 72 277 individuals of 10 species were counted in 2009 (332 hr of observation) and 2010 (465 hr), respectively. Eighty percent of bulk passage occurred in 29–38 d, with the average median passage date occurring in mid-March. Oriental Honey-buzzard (Pernis ptilorhyncus) made up 85.9 ± 2.9% of the flight, followed by Black Baza (Aviceda leuphotes, 8.7 ± 3.8%) and Chinese Goshawk (Accipiter soloensis, 3.0 ± 2.0%). The timing of the peak daily count differed among the three major migrants with highest count of Oriental Honey-buzzards occurring at 1200–1300 H, whereas for both Black Bazas and Chinese Goshawks, peak daily counts were at 1400–1600 H (when air temperatures were the highest). Most migration occurred during days when winds were from southwest and west. The difference in migration timing is believed to be associated with the species' flight behaviors, their preferred wind direction, and the availability of thermals. The height of flight for Oriental Honey-buzzards, which used both soaring and flapping flight during migration, was positively correlated with the hourly temperature (r = 0.241, P = 0.026). Results from migration counts made at Tanjung Tuan suggest that this watchsite captures a high proportion of migratory raptors (especially for Oriental Honey-buzzards) along the East Asian-Australasian flyway. Such information, together with count data collected from other watchsites, is essential for a better understanding of migratory raptors in this region and for effective conservation.